Relationship Between Foreign-Aid and Economic Growth: From The Evidence of Nepal - Sapkota, Liladhar (AMC Journal (Dhangadhi), 2024)
This study has empirically examined the relationship between the foreign aid and economic growth of the nation from the evidence of Nepal. The GDP has considered as proxy variable for economic development and independent variables are official developmental assistance (ODA), and capital formation (CF). This study has empirically analyzed the time series data since 1975 to 2011. Firstly, the stationarity has tested to find out whether the data are stationary or not. The data found non-stationary and the data are transferred into stationary. Then further regression analysis has done considering lnGDP as dependent variable and natural log of official development assistance and natural log of capital formation as independent variable. The model does not incorporate multicollinearity, heteroskedas city, and autocorrelation problem. The result found that there is negative relationship between GDP and ODA but positive relationship between capital formation and GDP. In nutshell there is negative relationship between foreign aid and economic growth of the nation, which is consistent with all the previous studies and contrasts with Anis C., and Iman S. (2005).